Analysis of the Effect of Green Banking and Financial Performance on the Profitability of Member Banks of the Indonesian Sustainable Finance Initiative - Nurdinsi Utama, Julius; Nirmala, Tiara; Andrian, Thomas; Herlina, Nurbetty; Ciptawaty, Ukhti (Lafadz Jaya Publisher, 2024)
This research examines the influence of the variables green banking (Green banking Index), Capital adequacy (CAR), Non-performing loans (NPL), Bank Efficiency (BOPO), Liquidity level (LDR) on the profitability of Member Banks of the Indonesian Sustainable Finance Initiative. This research uses a purposive sampling technique, 8 companies were sampled in the research as Member Banks of the Indonesian Sustainable Finance Initiative, namely: Bank Mandiri, Bank Rakyat Indonesia, Bank Negara Indonesia, Bank Central Asia, Maybank, Bank CIMB Niaga, Bank OCBC NISP and West Java Bank. This research examines economic data based on panel data, based on the calculation results it is found that banking ratios in the form of capital adequacy (CAR) and liquidity level (LDR) partially have a positive and significant effect in increasing Bank Profitability (ROA) of Members of the Indonesian Sustainable Bank Initiative, while the ratio Non-performing loans (NPL), Bank Efficiency (BOPO) and the Green Banking variable (Green Banking Index) have a negative and significant effect on (ROA) Members of the Indonesian Sustainable Bank Initiative.